2017
DOI: 10.1525/elementa.255
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of atmospheric and river inputs of black carbon, and impacts on biogeochemical cycles in Halong Bay, Vietnam

Abstract: Mari, X, et al. 2017 Seasonal dynamics of atmospheric and river inputs of black carbon, and impacts on biogeochemical cycles in Halong Bay, Vietnam. Elem Sci Anth, 5: 75. DOI: https://doi.org/10.1525/elementa.255 , respectively. Dissolved BC (DBC) concentrations averaged 2.6 µmol C L -1 in both the SML and ULW. Seasonal variations indicated that PBC concentration in the SML was controlled by atmospheric deposition during the dry season, while riverine inputs controlled both PBC and DBC concentrations in ULW d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 75 publications
0
16
1
Order By: Relevance
“…To our knowledge, the effect of pH on the physical properties of natural ocean OM has been little investigated (Mari et al, 2017). However, a huge volume of literature exists concerning the effect of pH and other parameters in marine and sewage-sludge EPS, including divalent ions and salinity, on flocculation and adsorption of OM, particularly in membrane filtration (Baudez et al, 2011;Pilli et al, 2015;Villacorte et al, 2015;Zhang et al, 2016).…”
Section: Acidificationmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the effect of pH on the physical properties of natural ocean OM has been little investigated (Mari et al, 2017). However, a huge volume of literature exists concerning the effect of pH and other parameters in marine and sewage-sludge EPS, including divalent ions and salinity, on flocculation and adsorption of OM, particularly in membrane filtration (Baudez et al, 2011;Pilli et al, 2015;Villacorte et al, 2015;Zhang et al, 2016).…”
Section: Acidificationmentioning
confidence: 99%
“…Some BC enters the coastal ocean in the dissolved (<0.8 µm) form in river runoff, However, most of it enters the global ocean through deposition of airborne, particulate BC (Mari et al, 2017). Airborne BC is part of the family of atmospheric aerosols.…”
Section: A Decreasing Trend In Production and Deposition Of Black Carbonmentioning
confidence: 99%
“…For example, the Bay is located a few tens of kilometers from the largest industrial zone and trading harbor in Vietnam (i.e., Haiphong) and is bordered in the North by open coal mining. In addition to these local sources, northern Vietnam is impacted by atmospheric BC originating from China during the dry season (B Guinot, personal communication; Mari et al, 2017). Altogether, these intense human activities result in high deposition of BC onto the surface waters of Halong Bay.…”
Section: Study Sitementioning
confidence: 99%
“…In the water column, DBC represents from 1 to 7% of the pool of dissolved organic carbon (DOC) (Mannino and Harvey, 2004;Ziolkowski and Druffel, 2010). The contribution of PBC to the pool of suspended particulate organic carbon (POC) in surface waters decreases from >50% in highly BC-impacted coastal zones (Mari et al, 2017a) to <3% in oceanic surface waters (Fang et al, 2016). Finally, in the surface microlayer (SML), which represents the interfacial boundary layer (typically 40-100 µm thick) between the atmosphere and the ocean (Wurl et al, 2017, and references herein), and which constitutes the main entrance gate for BC into the ocean, BC concentration can be very high and contribute from 11 to 97% of the pool of POC (Mari et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…In the atmosphere, BC is associated with other aerosols, the input of BC to the marine environment may lead to an enrichment in BCassociated elements, such as organic carbon (Willey et al, 2000;Raymond, 2005), nutrients (Mahowald et al, 2008;Kanakidou et al, 2012;Wang et al, 2015), trace metals (Paytan et al, 2009;Ito, 2013), and even pesticides (Kunz et al, 2005), potentially altering the structure and activity of phytoplankton (Paytan et al, 2009;Guo et al, 2012) and bacterial (Cattaneo et al, 2010;Mari et al, 2014;Pradeep Ram et al, 2018) communities. In addition, it has been shown that the BC introduced into marine surface waters sorbs dissolved organic matter (DOM), nutrients and small particles, and stimulate aggregation processes (Mari et al, 2014(Mari et al, , 2017a. The introduction of BC to the surface of the ocean may alter the initial steps of the biological carbon pump, i.e., DOM cycling and marine snow aggregate formation (Mari et al, 2014(Mari et al, , 2017a.…”
Section: Introductionmentioning
confidence: 99%